Analysis of Writing Errors and Its Implications in Learning Writing Skills - Ardyansyah Ardyansyah; Danial Hilmi (University of Darussalam Gontor, 2021)
Writing is one of the language skills, but the majority of students think writing is a difficult activity so they experience errors, especially in terms of imla'. This study aims to describe and analyze the forms of writing errors in student writing, factors affecting the writing errors, and the implications of writing errors in learning writing skills for students in al-Nasyiin al-Islami Pesantren Pamekasan Madura. This research uses qualitative research. To achieve these objectives, researcher uses the Glesser and Strauss model to analyze data called the fixed comparison model consisting of four steps, it is data reduction, data categorization, coding, and preparing working hypotheses. The results of this study are: Writing errors in the writing of the students at al-Nasyiin al-Islami Pesantren, is errors in adding letters, subtracting letters, writing letters that sound alike, changing letters or words, separating letters or words, writing hamzah on alif, connecting letters or words, writing hamzah qatha', writing hamzah on wawu; The Factors that influence writing errors in the writing of students al-Nasyiin al-Islami Pesantren come from the student side and the teacher side; The implications of this writing error are the number of errors in writing perfect sentences, changes in the meaning of vocabulary from the original meaning, some students are not able to write sentences perfectly, and the number of errors in the application of Arabic rules. Therefore, teachers must pay attention to these errors through student writing analysis so that they can find solutions to problems faced by teachers and students to improve learning writing skills.